Evaluate the Impact of the Use of Control Data Types on the Accuracy of Aerial Triangulation of the Images Taken by Unmanned Aerial Vehicle (Drones): Evaluate the Impact of the Use of Control Data Types on the Accuracy of Aerial Triangulation of the Images Taken by Unmanned Aerial Vehicle (Drones) - الخليل, عمر (Latakia University Journal -Engineering Sciences Series, 2022)
Abstract Some drones carry digital cameras equipped with the ability to record the location of each image captured in the GNSS system, which permit to obtain input data for aerial triangulation. In this paper, we discuss the effect of the types of reference data used in the aerial triangulation of drone images on the spatial accuracy of this triangulation. Here, we discuss the accuracy of aerial triangulation of the images taken by a GNSS RTK-based drone without postprocessing, and by a GNSS PPK-based drone which applies corrections to camera positions and orientations. The results demonstrated that the use of set points with RTK-equipped drones significantly improves the absolute accuracy of aerial triangulation and the graphical scales of cartographic products based on images of these drones (the absolute accuracy on control points improved from 95.03 cm to 42.09 cm in our example). On the other hand, we found that the use of ground control points with PPK-equipped drones does not significantly affect the absolute accuracy of triangulation and the graphical scales of cartographic products based on images of these drones. The absolute accuracy on the control points changed from 6.35 cm to 6.25 cm in our example, which is an imperceptible change. Keywords: Unmanned aerial vehicle, Aerial triangulation, global navigation satellite system, real-time kinematic processing, control points.